The stress levels of parents of premature infants and related factors in Nenoatal Intensive Care Units - Çekin, Burcu; Turan, Türkan (The Turkish Journal of Pediatrics, 2018)
The aim of this study is to determine the stress levels of parents whose premature baby are hospitalized in the neonatal intensive care unit (NICU) and to determine the factors affecting their stress. The study sample included 101 parents of premature babies in the NICU of a university hospital. Interviews were conducted with the parents. Additionally, the Parental Stress Scale: Neonatal Intensive Care Unit (PSS:NICU) was administered. When the stress levels of parents in the NICU were analyzed, it was found that their scores on the infant`s appearance and behaviors subscale of the PSS:NICU reflected the highest rate of stress. The mean score on the parental role alterations subscale was higher among mothers than fathers (p < 0.05). Additionally, high stress levels were found among parents who had children other than their baby in the NICU, parents whose baby had a young gestation age and a low birthweight, parents whose baby was on a respiration device, and parents who had experienced a stressful event in the past year. The stress levels of parents whose premature baby was hospitalized in the NICU were also high. The family-centred approach is recommended to identify and meet all the needs of all such parents.
Keywords: NICU; parents; premature baby; stress level